Der Funktionswandel der Villen im Veneto - eine kulturgeographische Analyse - Krings, Thomas (ERDKUNDE, 1990)
The aim of this contribution is to analyse the development of the Venetian villa, which has become one of the most intrinsic elements of the landscape in north-eastern Italy since the 15th century. In comparison with the Tuscan villa-fattoria system, which developed during the 13th century around the urban republics like Florence, Lucca and Pistoia, the Venetian villa is historically a late phenomenon. It began to flourish only since the 16th century after the decline of oriental trade, when the Venetians were obliged to obtain political control over their hinterland territories (terra ferma). The ideological justification for the colonization of the terra ferma was based on numerous articles by A. Cornaro, L. B. Alberti and A. Palladio in recollection and reinterpretation of Roman tractates on agriculture which praised agriculture as a holy activity. Since 1530, the first classic Venetian villas, combining agricultural and residential functions, were built. The extended villa lands were sub divided into numerous small tenant holdings. Until the middle of the 17th century the dominant form of contract was the mezzadria; after that period the cesure system was established (tenants who paid an annual rent in the form of money). In the following times the fragmentation of the villa lands hindered an increase of productivity. In the 18th century the type of the villa suburbana, with mainly residential functions, developed. With the fall of the Republic of Venice in 1797, the classical period of the Venetian villa ended.